Impact of combined additional resections on the surgical outcomes of robot-assisted resection of thymic epithelial tumors - Niedermaier, Benedikt Walter; Khan, Nabil; Eichhorn, Florian; Zehentmeier, Maria; Grosch, Heidrun; Griffo, Raffaella; Campisi, Alessio; Margineanu, Antonia; Allgäuer, Michael; Christopoulos, Petros; Thomas, Michael; Winter, Hauke; et al. (Journal of surgical oncology, 2025)
Background and Objectives Robot-assisted thoracoscopy (RATS) is rapidly emerging as the preferred approach for the resection of thymic epithelial tumors (TET). Current challenges include the role of RATS in locally advanced disease and combined additional resections. Methods This single-center study included all consecutive robot-assisted surgeries for TET performed between 2018 and 2024. We report perioperative outcomes and findings from a large center for robotic surgery center. Results One hundred and forty-three patients underwent RATS for the resection of histologically confirmed TET, including 130 (91%) patients with thymoma and 13 (9%) patients with thymic carcinoma. The median tumor size was 54 mm (35.5-75) and most patients presented in a localized stage of disease, with 120 patients (83.9%) in TNM stage I (TNM 8th edition). The conversion rate to open surgery was 4.2% and R0 resection was achieved in 134 (93.7%) patients. Combined extended resections that included lung, pericardium or great vessels were performed in 44 (30.8%) patients and were the only independent predictor of postoperative complications in a multivariable logistic regression model (OR 2.87; p = 0.03). Conclusions Robot-assisted surgery is feasible and without unexpected safety concerns for TET. Combined extended resections, often necessary for locally advanced disease, are a significant predictor of postoperative complications.